2007
DOI: 10.1158/1078-0432.ccr-06-1603
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Idiotype Vaccination Combined with Interleukin-12 (IL-12), or IL-12 and Granulocyte Macrophage Colony-Stimulating Factor, in Early-Stage Multiple Myeloma Patients

Abstract: Purpose and Experimental Design: Twenty-eight patients with immunoglobulin G myeloma stages I to II were immunized i.d. over 110 weeks with autologous M protein combined with interleukin-12 (IL-12; n = 15) or with IL-12 and granulocyte macrophage colony-stimulating factor (GM-CSF; n = 13). Idiotype-specific T-cell responses were assessed by [ 3 H]thymidine incorporation, enzyme-linked immunospot assay, and delayed-type hypersensitivity reaction. Results: Based on these three assays, idiotype-specific immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…idiotypic vaccination in MM). 26,27 Interestingly, our study showed that LTDC-MM patients have lower numbers of Treg cells than do symptomatic MM patients, particularly in the BM. Despite a large body of evidence that points to increased numbers and a functionally effective status of Treg cells in both hematologic and non-hematologic malignancies, 28 the results reported in MM are controversial, which is probably related to the different methodologies and techniques used to identify the cells.…”
Section: Discussionmentioning
confidence: 63%
“…idiotypic vaccination in MM). 26,27 Interestingly, our study showed that LTDC-MM patients have lower numbers of Treg cells than do symptomatic MM patients, particularly in the BM. Despite a large body of evidence that points to increased numbers and a functionally effective status of Treg cells in both hematologic and non-hematologic malignancies, 28 the results reported in MM are controversial, which is probably related to the different methodologies and techniques used to identify the cells.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, idiotype vaccination combined with IL-12 or IL-12 and GM-CSF 30 and the injection of cytokine-matured dendritic cells 31 have been reported to increase Tregs frequency in MM patients, providing further explanation as to why these strategies have fallen short of clinical expectations. More recently, thalidomide and lenalidomide have also been shown to increase the frequency and function of Tregs in MM, and lenalidomide, in association with dexamethasone, has been reported to increase Tregs and concurrently decrease the effector functions of T and NK cells.…”
Section: Foxp3mentioning
confidence: 99%
“…GM-CSF/IL-12 has been used in multiple myeloma patients, where the combined actions of both cytokines led to a reduction in circulating tumor B cells [75][76][77]. Idiotype-specific immune responses were observed in the majority (75-85%) of patients treated with both GM-CSF and IL-12, as compared to 20-30% of the patients treated with IL-12 alone, and were inversely correlated with the frequency of CD4 + /CD25 + T regulatory cells.…”
Section: Granulocyte-macrophage Colony-stimulating Factor (Gm-csf)/il-12mentioning
confidence: 99%